Exclusive Breastfeeding Increased by an Internet Intervention - Giglia, Roslyn; Cox, Kylee; Zhao, Yun; Binns, Colin (Mary Ann Liebert, Inc. Publishers, 2015)
Background: Exclusive breastfeeding for 6 months is acknowledged universally as the optimal feeding method for infants in order to provide the greatest health and well-being gains for the infant and mother. Despite this, many women stop short of attaining this desired outcome for their infant. With the permeation of the Internet into most of society, the aim of this study was to evaluate the effect of a breastfeeding support Internet intervention on breastfeeding outcomes on women living in regional Western Australia. Materials and Methods: A nested intervention design within a longitudinal cohort titled the Regional Infant Feeding Study examined the effect of an Internet support Web site on the infant feeding practices of women living in regional Western Australia. Results: In total, 414 women participated in the Internet study and were randomly assigned to the control group (n=207) or the intervention group (n=207). Women enrolled in the intervention were significantly more likely to be exclusively breastfeeding at 6 months postpartum compared with control group participants. Those women experiencing breastfeeding problems were more likely to access the Internet. Conclusions: This breastfeeding support intervention study demonstrated a positive effect on longer-term exclusive breastfeeding for those enrolled in the intervention group. Together with more traditional methods of support, the Internet provides another possible method for promoting positive long-term breastfeeding outcomes.